Land Value Impacts of Metro Line 1 in the Districts of San Borja and Surquillo, Lima -Perú (2023) - Vidal Matos, Marybel (2024)
In the global context, there is a growing trend to incorporate mechanisms for land value capture into public policies to address challenges associated with the financing of public transportation infrastructure. For a proper assessment, it is crucial to gather information on the impacts of public actions that generate value in private assets, and such information is scarce in the Peruvian context. The main objective of the research was to estimate the impact of Metro Line 1 on housing sales price around three stations in the San Borja - Surquillo district in Lima, Peru. A quantitative methodology was proposed, with an explanatory approach, non-experimental design, and cross-sectional design (2023), for a refined sample of 339 residencial properties surrounding the La Cultura, San Borja Sur, and Angamos stations of Line 1 of the Lima Metro using available information from real estate websites. The evaluation focused on estimating a hedonic pricing model that explains variations in housing sales price based on their structural attributes, neighborhood characteristics, safety attributes, and distance to the nearest station of Metro Line 1. The results show the marginal impact of a unit increase in the distance between the property and the nearest Metro station on the percentage change in the sale price, with an increase of 0.043% for residential properties up to 100m, 0.33% up to 400m, 0.21% up to 800m, and decreasing influence up to a maximum radius between 1200 to 1300 meters.